The first record of Ennearthron Mellié, 1847 (Coleoptera: Tenebrionoidea: Ciidae) in the Southern Hemisphere, with the description of a distinctive new species - Lopes-Andrade, Cristiano; Zacaro, Adilson Ariza (Zootaxa, 2003)
This paper presents the description of Ennearthron victori sp. nov. In contrast to all known species of this genus, E. victori is the first one occurring in the Southern Hemisphere (Neotropical Region, Brazil, Minas Gerais and São Paulo States) and, the only one in which males lack a fovea on the first ventrite.